2022
DOI: 10.1111/imj.15049
|View full text |Cite
|
Sign up to set email alerts
|

Direct oral anticoagulants for cancer‐associated venous thromboembolisms: a systematic review and network meta‐analysis

Abstract: Background: Several recent randomised controlled trials (RCT) have investigated the use of direct oral anticoagulants (DOAC) in the treatment of malignancy-associated venous thromboembolism (VTE).Aims: This meta-analysis combines all RCT data to determine the risks of recurrent VTE and bleeding with DOAC in patients with malignancy-associated VTE compared with low-molecular-weight heparin (LMWH). Methods:The study followed PRISMA guidelines. MEDLINE, EMBASE and CENTRAL were systematically searched from incepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 40 publications
0
14
0
1
Order By: Relevance
“…At the time the search was ended (October 6, 2020), 46 records were identified, of which 26 were discarded on title and abstract ( n = 24) or full‐text ( n = 2). The 20 remaining meta‐analyses were published in nonpredatory peer‐reviewed journals: five studies pooled the data of two RCTs, 6‐10 four studies pooled the data of three RCTs, 11‐14 and 11 studies pooled the data of four RCTs 15‐25 . The main characteristics of the 20 meta‐analyses are described in Table 1 and the results of the 20 meta‐analyses for efficacy and safety endpoint are shown Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time the search was ended (October 6, 2020), 46 records were identified, of which 26 were discarded on title and abstract ( n = 24) or full‐text ( n = 2). The 20 remaining meta‐analyses were published in nonpredatory peer‐reviewed journals: five studies pooled the data of two RCTs, 6‐10 four studies pooled the data of three RCTs, 11‐14 and 11 studies pooled the data of four RCTs 15‐25 . The main characteristics of the 20 meta‐analyses are described in Table 1 and the results of the 20 meta‐analyses for efficacy and safety endpoint are shown Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…The 20 remaining meta-analyses were published in nonpredatory peer-reviewed journals: five studies pooled the data of two RCTs, 6-10 four studies pooled the data of three RCTs, [11][12][13][14] and 11 studies pooled the data of four RCTs. [15][16][17][18][19][20][21][22][23][24][25] The main characteristics of the 20 meta-analyses are described in Table 1 and the results of the 20 meta-analyses for efficacy and safety endpoint are shown Figure 1. Within each category of meta-analysis (two, three, or 4 RCTs), the results were similar regarding the risks of VTE recurrence (differences in pooled relative…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…These trials indicated that oral treatment with a factor Xa inhibitor may be an alternative to subcutaneous LMWH for selected CAT patients, and this statement was eventually adopted in the current guidelines. However, DOACs may be associated with an increased risk of bleeding in patients with gastrointestinal and potentially genitourinary cancer [14]. In fact, there seems to be a higher risk for mucosal bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, there seems to be a higher risk for mucosal bleeding. Moreover, potential interactions need to be checked before use of DOACs [14]. These and similar precautions for the use of DOACs are included in several guidelines including those of the ASCO [15] and the National Comprehensive Cancer Network [16].…”
Section: Discussionmentioning
confidence: 99%
“…Respecto de las hemorragias graves, los AOD presentaron menor incidencia en dos ensayos (ambos con apixabán) y mayor incidencia en los otros dos, si bien globalmente las diferencias no fueron significativas en 3 de los 4 ensayos (rivaroxabán en un ensayo y apixabán, en dos) (Tabla III). Son aspectos particulares de estas RS/M que las hemorragias son más frecuentes en los cánceres gastrointestinales (50) y que apixabán presenta el mejor perfil de seguridad (52,54).…”
Section: Eac En Poblaciones Específicas (Etv Y Cáncer)unclassified